Antibodies against Fibrinogen in Pregnant Women, in Post Delivery Women and in the Newborns - Kondera-Anasz, Zdzislawa (Thrombosis and Haemostasis, 1998)
Pregnancy and delivery have measurable effects on haemostatic and immunological changes. Degradation of fibrinogen induces significant structural and conformational modulation and leads to the progressive loss of antigenic sites present on the parent molecule but also exposes some new sites. These neoantigens may be recognized by the immune system and may be elicited by the autologous host manifested by the production of autoantibodies. Therefore in the present study, in pregnant and post delivery women and in the newborns, levels of antibodies against fibrinogen, fibrin(ogen) degradation products (FDP) and fibrin degradation products (D-dimer) were examined.Enzyme immunoassay (ELISA) was used to detect and quantitate autoantibodies against fibrinogen (class G immunoglobulin) in human sera. In all sera there were found varying concentrations of autoantibodies and their levels were significantly higher in all pregnant women in comparison with non-pregnant ones. Significantly higher levels were found in Rh immunized and clinically complicated pregnancies.The level of autoantibodies, coagulation and fibrinolytic system components were higher in post delivery women than in normal pregnant women. Also antibodies to fibrinogen were studied in cord serum of newborns in different terms of delivery. The low levels of antibodies in all newborns raise questions of possible foetal-maternal immunologic interactions. Positive correlation between mothers and newborns was demonstrated after delivery at gestational age from 34th to 41st week, and negative in 42nd and more week. There were no significant differences in antibody level among the newborns delivered by the same mothers.It was found that autoantibodies bind selectively to the fibrinogen and fibrinogen fragments X, Y and D. These autoantibodies may represent a new interface between the coagulation and the immune systems which may be significant in controlling the pathologic activities of the cleavage fragments.